Samuel Appleton Storrow correspondence - Storrow, Samuel Appleton, -1837.
Fragment of a letter written by Storrow to his sister regarding a family friend, Ann Hill Carter Lee, and her marriage to Virginia governor Henry Lee.
Negative photocopy.
Judge advocate, U. S. Army. Born 1787.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lee, Ann Hill Carter, -- 1773-1829.; Lee, Henry, -- 1756-1818.; Army officers